Culturally responsive practice and the role of school administrators - Minkos, Marlena L.; Sassu, Kari A.; Gregory, Jess L.; Patwa, Shamim S.; Theodore, Lea A.; Femc-Bagwell, Michele (Psychology in the Schools, 2017)
In recent years, student populations within public schools in the United States have become increasingly diverse, both culturally and linguistically, and are projected to continue to grow in diversity in the future. Consequently, educators must be prepared to support the needs and education of students with multicultural backgrounds who may differ from them. School administrators play an important role in creating safe, accepting school environments and guiding the education of diverse student populations. However, there is a need for additional guidance for school leaders in cultivating schools that promote equity for all students. Using the National Policy Board for Educational Administration (NPBEA) Professional Standards for Educational Leaders as a guiding framework, this paper provides practical suggestions regarding culturally responsive strategies and practices that school administrators might employ in leading diverse school communities.
15 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000415935300007, lens.org/072-893-262-948-380 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: culturally responsive practice; dept.csp; dept.edl; diversity; educational leadership; peer-reviewed

Trust relationships in schools: supporting or subverting implementation of school-wide initiatives - Gregory, Jess L. (School Leadership & Management, 2017)
This article explores trust relationships in schools that involve disparities in power. Trust is a key factor in developing a positive school culture and strong leadership in schools. Even with the flattening of hierarchies through more distributive models of leadership, disparities in power exist and they influence the trust relationships in schools. Through both French and Raven’s and Follett’s conceptualisations of power, five brief autobiographical stories about trust in schools are deconstructed. Lessons for leadership are gleaned from the power relationships in the autobiographical stories of trust shared by public school educators. In addition, general recommendations are offered that are relevant for all levels of school leadership including but not limited to the instructional coach, the curriculum supervisor, the building principal, and the classroom teacher.
8 citations (Crossref) [2023-10-31]
Keywords: Follett; French & Raven; Trust; change leadership; dept.edl; educational leadership; power

Improving student achievement through strengthening principal and school counselor partnership - Yavuz, Olcay; Cayirdag, Nur; Dahir, Carol; Gümüşeli, Ali İlker (International Journal of Educational Reform, 2017)
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/020-647-036-070-16X, pop00220 tex.type: [object Object]
Keywords: dept.edl; peer-reviewed

School principal perceptions of the school counsellor's role: Traditional or transformed? - Yavuz, Olcay; Dahir, Carol; Gumuseli, Ali Ilker (Journal of Educational Leadership, Policy and Practice, 2017)
There is a continued emphasis on the importance of building collaborative working relationships between school principals and counsellors to address the growing academic, career and college readiness, and social-emotional needs of students in K-12 schools. This study explored and analysed 1466 school principals' perceptions around important school counselling priorities, perceptions, and activities that are carried out in Turkish public and private schools. The study additionally explored school principals' expectations of school counsellors' roles and responsibilities as aligned with traditional and transformed school counselling programmes and practices. This study may be of value to school leaders, policy makers and educators interested in revising and improving their school counselling services to meet the complex academic and counselling needs of students in contemporary schools.
Keywords: dept.edl; ⛔ No DOI found

Attitudes of Croatian and Polish elementary school teachers towards inclusive education of children with disabilities - Cwirynkalo, Katarzyna; Kisovarivanda, Tamara; Gregory, Jess L; Żyta, Agnieszka; Arciszewska, Aleksandra; Zrilic, Smiljana (Hrvatska Revija za Rehabilitacijska Istraživanja, 2017)
Inclusive education has been gaining increasing attention from governments throughout the world. Croatia and Poland, two European Union members that ratified the Convention on the Rights of Persons with Disabilities, have been working on issues related to improving the quality of education of children with special educational needs. The aim of this article was to explore the attitudes of Croatian and Polish elementary education teachers towards inclusion of these children in regular classes. The sample consisted of 98 elementary education teachers from Croatia (N=50) and Poland (N=48). A diagnostic survey based on the Teacher Attitudes Toward Inclusion Scale (TATIS) (Cullen, Gregory, & Noto, 2010) was used. The instrument allows measurement of three main components of attitudes: teacher perceptions of students with mild to moderate disabilities (POS), their beliefs about the efficacy of inclusion (BEI), perceptions of professional roles and functions (PRF), as well as their general attitudes towards inclusion. We found that Polish teachers received significantly higher scores on two subscales: POS and BEI. We also found that age and place of living influenced the attitudes of teachers in the two groups. Implications for practice are discussed. © 2017, University of Zagreb, Faculty of Political Sciences. All rights reserved.
Citation Key Alias: lens.org/154-714-360-054-192 tex.type: [object Object]
Keywords: Children with disabilities; Inclusive education; Teachers’ attitudes; dept.edl; ⛔ No DOI found

Mindfulness as a prerequisite to effective leadership; exploring the constructs that foster productive use of feedback for professional learning - Day, Danette V; Gregory, Jess L (Interchange, 2017)
This paper proposes a model that integrates mindfulness, ego, and mindset as filters of the information available for professional learning. The paper explores connections between mindset, ego, and mindfulness that promote or inhibit an educator’s ability to use feedback for learning. A leader’s commitment to creating spaces for meaningful use of all types of feedback promotes a school climate that encourages risk taking in learning. Mindfulness, the cultivation of the ability to pay attention to the present moment non-judgmentally, is a prerequisite skill to the effective delivery and use of feedback to promote professional learning. The development of mindfulness requires practice of a method and the continual application of mindfulness to remain open to learning from feedback. © 2017, Springer Science+Business Media B.V.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-616-943-494-687 tex.type: [object Object]
Keywords: Effective leadership; Ego; Feedback; Mindfulness; Mindset; Professional learning; dept.edl

Instructional scaffolding to promote an autonomous learner - Gregory, Jess L (Preparing Pre-Service Teachers for the Inclusive Classroom, 2017)
An autonomous learner has developed an intrinsic motivation that drives him or her to pursue learning for the inherent satisfaction and enjoyment that stems from the acquisition of knowledge. This chapter presents strategies for teachers to develop a classroom of more autonomous learners. In addition to some strategies and sequencing of activities to maximize their impact, the chapter presents Universal Design for Learning as a framework for thinking about all teaching and ways to apply differentiated instruction to meet the needs of all learners. While there is a focus on the experience of a novice teacher, the content of this chapter is relevant for all educators looking to reinvigorate their practice to empower students to be more in command of their own learning.
Citation Key Alias: lens.org/149-445-063-289-055
Keywords: dept.edl